Aktuelle Entwicklungen bei der Vergütung von Vorständen in DAX-Unternehmen - Markus Eigruber; Klaus Haider; Thomas Pfeiffer; Christian Schmid (Swiss Journal of Business, 2025)
his article provides insights into current trends and developments in executive compensation at German DAX companies. We discuss the implementation of sustainable ESG remuneration components, malus and clawback provisions, say-on-pay, and relative performance measurement. For this purpose, we examine compensation reports of DAX companies for the fiscal years 2020 to 2023. The results show that ESG performance measures are mostly used in both short-term and long-term variable compensation and that they cover all dimensions of ESG. ESG goals that are frequently mentioned include the reduction of greenhouse gas emissions and measures for diversity and inclusion. Clawback provisions are now part of the executive compensation in all DAX companies, and only in exceptional cases do shareholders reject the compensation system or compensation report. Relative performance evaluation is only used in the context of long-term incentives and is based on stock price-based performance measures.